2019
DOI: 10.33603/rill.v2i3.2138
|View full text |Cite
|
Sign up to set email alerts
|

Employing Jigsaw in English Academic Writing: An Action Research in an Efl Class in Indonesia

Abstract: The aims of the study were to get increasing of students’ English academic writing ability through the jigsaw technique. It is done in the English Education Program Study of Postgraduate Program Universitas Indraprasta PGRI Jakarta. In this study has emphasized teamwork learning. The research approach is mixed research using action research method. The process of collecting data used test, observation, documentation, interviews, and daily note. The technique of data analysis used qualitative analysis and quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
(5 reference statements)
1
1
0
Order By: Relevance
“…The results corroborated several studies (Baron, 2019;Barrett, 2005;Chukwu & Dike, 2019;Evcim & Ipek, 2012;Maden, 2011;Mbacho & Changeiywo, 2013;Mohammed & Hamied, 2019;Oliveira, Vailati, Luiz, Boll, & Mendes, 2019;Sudrajat, Iasha, & Femayati, 2019;Suroto, 2017;Ward & Lee, 2005;Yoshida, 2018) which provide empirical evidences in the effectiveness of Jigsaw in enhancing student achievement in general.…”
Section: Figuresupporting
confidence: 85%
“…The results corroborated several studies (Baron, 2019;Barrett, 2005;Chukwu & Dike, 2019;Evcim & Ipek, 2012;Maden, 2011;Mbacho & Changeiywo, 2013;Mohammed & Hamied, 2019;Oliveira, Vailati, Luiz, Boll, & Mendes, 2019;Sudrajat, Iasha, & Femayati, 2019;Suroto, 2017;Ward & Lee, 2005;Yoshida, 2018) which provide empirical evidences in the effectiveness of Jigsaw in enhancing student achievement in general.…”
Section: Figuresupporting
confidence: 85%
“…Richards (2001) defines Jigsaw tasks as the tasks which involve learners to put different pieces of information to arrive at a whole. Proponents of Jigsaw describe this task as a modern method of cooperative learning which develops learners' autonomy and their teamwork skills (Baron, 2019;Zuo, 2011). Moreover, Sauro et al (2005) also showed that Jigsaw tasks are effective for both drawing learners' attention to form and helping them recall both the form and the function of the targeted form.…”
Section: Conclude Thatmentioning
confidence: 99%